2012
DOI: 10.1073/pnas.1207300109
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis protein GrgA activates transcription by contacting the nonconserved region of σ 66

Abstract: The bacterial RNA polymerase holoenzyme consists of a catalytic core enzyme in complex with a σ factor that is required for promoter-specific transcription initiation. Primary, or housekeeping, σ factors are responsible for most of the gene expression that occurs during the exponential phase of growth. Primary σ factors share four regions of conserved sequence, regions 1-4, which have been further subdivided. Many primary σ factors also contain a nonconserved region (NCR) located between subregions 1.2 and 2.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 31 publications
7
72
1
Order By: Relevance
“…1C, 2 A-C, and S1). Interacting with the primary σ-NCR is a property that RbpA shares with the unrelated Chlamydia trachomatis transcription factor GrgA, which binds to the Chlamydia trachomatis σ 66 -NCR (20). Moreover, although structurally distinct from RbpA, the holoenzyme assembly factor Crl from enteric bacteria interacts with the equivalent region of the group 2 σ-factor σ S (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…1C, 2 A-C, and S1). Interacting with the primary σ-NCR is a property that RbpA shares with the unrelated Chlamydia trachomatis transcription factor GrgA, which binds to the Chlamydia trachomatis σ 66 -NCR (20). Moreover, although structurally distinct from RbpA, the holoenzyme assembly factor Crl from enteric bacteria interacts with the equivalent region of the group 2 σ-factor σ S (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that Pgp4-DNA interactions require additional protein partners for successful DNA binding to occur. Of note, it has recently been reported that efficient transcription activation of several promoters by a chlamydial specific transcription factor, general regulator of genes A (GrgA), in vitro requires contact with both DNA and a portion of a nonconserved region of the primary factor, 66 , of C. trachomatis (53). Studies are under way to determine the molecular mechanism of Pgp4-mediated gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy allows a chlamydial gene to be controlled by multiple regulatory signals and to have a hybrid temporal expression pattern that may not be possible with a single promoter. Chlamydia has a limited means to differentially regulate its genes because it has only about a dozen transcription factors (6,19,(22)(23)(24). Tandem promoters provide a relatively simple approach to fine-tune the expression of a chlamydial gene by using existing mechanisms of temporal regula-…”
Section: Discussionmentioning
confidence: 99%